New Insights into the Pathogenesis and Treatment of Urinary Tract Infections - Carmelo Biondo (Pathogens, 2023)
About 150 million people around the world experience urinary tract infections (UTI) every year, with adult women 30 times more likely to develop a UTI than men [...]